Tingkat Pengetahuan Erosi Gigi pada Mahasiswa Profesi di Rumah Sakit Gigi dan Mulut Jakarta - Alisa Novianty Pratiwi; Okky Marita Ardy (Majalah Sainstekes, 2020)
The aim of this cross-sectional study was to assess knowledge related to tooth erosion among dental students in dental hospital, Jakarta. Data were collected by means of a self-applied questionnaires that were distributed among 90 participants from three dental hospitals in Jakarta. The response rate was 100 percent. Chi-square and Mann-Whitney tests were used for statistical analysis (p less than 0.05). The majority of the participants had heard about erosion (95.6 percent). 33.3 percent of the students almost had not seen a patient with erosion, and 37.8 percent reported they saw a patient with erosion in a month at their dental hospital. 90 percent of the students were knowledgeable and well-prepared to diagnose the condition.